Influence of two methods of CaCl2 application and concentrations used to maintain passion fruit firmness - da Silva, A. P.; Vieites, Rogério Lopes [UNESP] (Fundacion Romulo Raggio, 2000)
This is a report on the influence of the methods of postharvest application of CaCl2 in several concentrations, on the maintenance of the firmness of the sweet passion fruit (Passiflora alata Dryander). The fruits, picked in the pre-climateric stage, were selected desinfection with thiabendazol and submitted to CaCl2 in concentrations of 0% (control), 1%, 2%, 3% or 4% with two methods: immersion (for 2 h) and infiltration under vacuum and pressure (- 25 vacuum kPa, for 1 minute and, + 25 pressure kPa, for 1 min). All fruits were stored under refrigeration (9 degreesC, 85-90% RH), for 30 d. The fruits were evaluated for texture every 3 d. From the results, it is concluded that application of CaCl2 by infiltration favored the maintenance of fruit consistency during the first 18 days of storage. Fruits treated with 1% and 2% of CaCl2 were firmer than the others.
Keywords: Passiflora alata; conservation; texture; firmness